PERANCANGAN SISTEM KONTROL OTOMATIS UNTUK PEMELIHARAAN DAN PERAWATAN MESIN COMPUTER STICHING (CSC) - Sukron Maulana, Iqbal; Susandi, Dony (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2019)
Along with the development of community growth, the development of industry also develops very quickly. This development includes people's purchasing power, people's interest in goods that have a high level of quality, thus enabling the community to make the most of these goods. based on observations made in the sewing section which is the most important part in the production process, found several problems that occur in the sewing process, such as the results of the skip stitches and bobbins that break easily. In writing this practical work report is discussed about how to overcome the results of the stitches that are skip to the computer stiching machine, how to overcome so that the bobbin thread does not break easily and when the bobbin thread will run out can be known. Based on observations during practical work, the disturbance that causes the skip stitching results is due to blunt needles and poor yarn quality. Overcome the problem by doing maintenance and maintenance of computer stiching machines according to schedule. While the interference causing the bobin thread to break easily is the condition of the Home Lifeboat and Rotary Hook in dirty condition, to prevent it can be applied to the microcontroller system by using Light Dependent Resistor (LDR) and Infrared proximity sensors to detect the cleanliness of the lifeboat's room and to control the bobbin thread when it will run out.